"Just there for the fashion, basically": politicized fem(me)ininity in the fat-o-sphere. Issue 1 (2nd January 2023) - Gibson, Gemma
ABSTRACT: Body positivity is experiencing a cultural moment of popularity. Recognizable by its self-love and "inclusive" messaging, body positivity's primary aim is to help people feel "good" in their bodies. However, the movement also receives legitimate critiques which argue only some bodies are celebrated. Fem(me)inine fat people are centralized in body positivity and with the popularization of branding influenced microblogging comes a very specific, cultivated femme style associated with popular fatshion. This article explores where fem(me)inine fatshion styles come from and whether femme is being recognized as a political identity in the body positivity and fat activist movements. Using case studies and autobiographies of people engaging with body positive ideologies, I examine the claims that body positivity depoliticizes the fat activist movement and explore whether this happened within a specific femme and fatshion context. I conclude that while embodying fem(me)ininity can feel like an act of resistance, it is unlikely all the goals of fat activism will be met through a "legitimized" fat fem(me)ininity alone.